Analisis Kemandirian Keuangan Daerah dalam Peningkatan Kesejahteraan Masyarakat di Kabupaten Kaimana - Fahriansyah Syam; Ahmad Zulfikar (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2022)
The background of this study is regional financial independence which is very low, yet dependence on the central government is very high in Kaimana Regency. This study aims to determine the level of regional financial independence in supporting community welfare improvement over the past five years, as seen from the analysis of financial ratios and human development index levels. The method used is qualitative descriptive research with an inductive approach. Data collection techniques are carried out by observation, semi-structured interviews, and documentation. The results showed that the level of financial independence of Kaimana Regency is still low in the last five years, namely from 2016-2020, with an average ratio of regional financial freedom is 3.82%, the average percentage of the degree of regional economic dependence is 95.67%, the moderate degree of fiscal decentralization is 3.67%, the average effectiveness of regional native income management is 111.54%, and the level of community welfare which is also still low with the average HDI is 63.63%. Based on the analysis results, the local government needs to issue strategic efforts by empowering regional potential that can be used as a source of provincial revenue to support the implementation of regional autonomy, which aims to improve the community's welfare.